Lithium: effects in animal models of vanishing white matter are not promising - Witkamp, Diede; Oudejans, Ellen; Hoogterp, Leoni; Hu-A-Ng, Gino V.; Glaittli, Kathryn A.; Stevenson, Tamara J.; Huijsmans, Marleen; Abbink, Truus E. M.; van der Knaap, Marjo S.; Bonkowsky, Joshua L. (Frontiers in Neuroscience, 2024)
Vanishing white matter (VWM) is a devastating autosomal recessive leukodystrophy, resulting in neurological deterioration and premature death, and without curative treatment. Pathogenic hypomorphic variants in subunits of the eukaryotic initiation factor 2B (eIF2B) cause VWM. eIF2B is required for regulating the integrated stress response (ISR), a physiological response to cellular stress. In patients' central nervous system, reduced eIF2B activity causes deregulation of the ISR. In VWM mouse models, the extent of ISR deregulation correlates with disease severity. One approach to restoring eIF2B activity is by inhibition of GSK3β, a kinase that phosphorylates eIF2B and reduces its activity. Lithium, an inhibitor of GSK3β, is thus expected to stimulate eIF2B activity and ameliorate VWM symptoms.The effects of lithium were tested in zebrafish and mouse VWM models. Lithium improved motor behavior in homozygous eif2b5 mutant zebrafish. In lithium-treated 2b4 he 2b5 ho mutant mice, a paradoxical increase in some ISR transcripts was found. Further, at the dosage tested, lithium induced significant polydipsia in both healthy controls and 2b4 he 2b5 ho mutant mice, and did not increase expression of other markers of lithium efficacy. In conclusion, lithium is not a drug of choice for further development in VWM based on the limited or lack of efficacy and significant side-effect profile.